Art as a generational and geographical transversal tool in the hands of youth: Srebrenica is Dutch history - Hasić, Fahira (International journal of transitional justice, 2022)
This article is about the role of youth in transitional justice and art as a medium in furthering that role. It examines Srebrenica Is Dutch History, a travelling memorial both by young people and about young people, as a transgenerational means for dealing with the past, and as an illustration of youth in transitional justice from the perspective of memorialization across both time and location. As much as this article is by me, it is also about me. It is a reflective exercise constituting my first act of ownership over my identities as a child of genocide survivors, a former refugee and a 23-year-old Bosnian-Belgian female scholar.